(untitled) (Acta Scientiarum. Health Sciences, 2016)
The objective of this study is to propose an action plan for the communication process in the nursing team. The theoretical references were: the model of a communication process proposed by Berlo and essential concepts of King´s Theory. It is a qualitative, convergent-care research. The data production technique was the semi-structured interview with 25 nurses of a public hospital. Data used the thematic content analysis technique. The elements of the communication team are: perception, self, space, time, stress, role, authority, power, status, audience, empathy and nonverbal communication. The plan proposes a dynamic, flexible, interactive and relational communication process, in order to contribute to the professional qualification and make new practices of care viable. It was concluded that its elements do not have a fixed and stable position, but throughout the process they are used according to the needs of each party.